Endoscopic submucosal dissection to relieve a flexure of the gastric conduit after esophagectomy - Yamamoto, Katsumi; Noro, Hiroshi; Sato, Yu; Kusakabe, Akira; Tatsumi, Nobuyuki; Michida, Tomoki; Ito, Toshifumi (Endoscopy International Open, 2018)
Background and study aims A 70-year-old-man underwent an esophagectomy and posterior mediastinal reconstruction for esophageal cancer that was curatively resected. Although the patient was allowed to eat after surgery, he repeatedly vomited after drinking water or eating meals and required continuous hospitalization. An upper gastrointestinal series and endoscopic examination revealed an obstruction due to the flexure of the gastric conduit, which was repeatedly treated with endoscopic balloon dilation. Endoscopic balloon dilation was completely ineffective, however, because the obstruction was not due to a small lumen diameter, but rather to severe flexure. We hypothesized that the power of contraction provided by ulcer scar formation after mucosal resection could straighten the flexure, and thus removed a piece of the mucosa 8 cm in diameter on the oral side of the flexure by endoscopic submucosal dissection (ESD) 4 months after the esophagectomy. Endoscopic examination on post-ESD Day 10 revealed that the gastric conduit flexure was straightened due to ulcer scarring, and obstruction at the flexure opened over time. Meals were restarted and the patient could eat without vomiting. He was discharged from the hospital 5 weeks after ESD. This is the first case report of obstruction due to flexure of the gastric conduit after esophagectomy that was successfully treated with mucosectomy using ESD. Mucosectomy using ESD may be an effective treatment option for obstruction due to flexure of the gastric conduit after esophagectomy.